INTERRELATIONS BETWEEN THE MYCORRHIZAL SYSTEMS AND SOIL ORGANISMS - BALAEŞ TIBERIUS; TĂNASE CĂTĂLIN (Journal of Plant Development, 2011)
The mycorrhizae are largely spread in natural ecosystems, and the proportion of plants that realise mycorrhizas is overwhelming, this relation involving advantages for both partners. The presence or absence of mycorrhizae, the rate and intensity of mycorrhiza formation are aspects with ecological importance, but also present importance in modern agriculture. The research results published on international literature which views the principal relations between mycorrhizae and soil microbiota, the way in which these relations affect the intensity of mycorrhizae formation and also the efficiency of mycorrhizae under the influence of soil organisms are synthesized and commented in this paper. The relations between mycorrhizae and different categories of bacteria, protozoa or microfungi, as well the influence of invertebrates through interactions of them with microorganisms are also being analyzed.